Suprathreshold Motion Perception in Anisometropic Amblyopia: Interocular Speed Matching and the Pulfrich Effect. Issue 6 (June 2019) - Maehara, Goro; Araki, Syunsuke; Yoneda, Tsuyoshi; Thompson, Benjamin; Miki, Atsushi
Abstract : SIGNIFICANCE: Our results indicate that the difference in perceived luminance between the amblyopic and fellow eyes that is present under dichoptic viewing conditions does not affect the perceived speed of suprathreshold motion stimuli. This finding provides a new insight into suprathreshold perception in amblyopia. PURPOSE: Interocular matching experiments indicate that dichoptically presented stimuli have a lower perceived luminance in amblyopic eyes relative to fellow eyes. This may be a consequence of interocular suppression. We investigated whether this effect extends to suprathreshold motion perception. METHODS: Participants with amblyopia and control observers matched the perceived speed of dichoptically presented random-dot kinematograms and the perceived luminance of gray patches. Control participants also performed the speed matching task with a neutral density filter over one eye to simulate a perceived luminance reduction. RESULTS: The amblyopia group exhibited lower perceived luminance in the amblyopic than in the fellow eye, as has previously been reported. However, interocular speed matching was veridical. For control observers, perceived speed was reduced in the eye with a neutral density filter relative to the nonfiltered eye. To assess whether the perceived luminance reduction in the amblyopic eye affected binocular function, we also measured the Pulfrich effect in the amblyopia group with equal luminance presented to each eye. No patients reported a spontaneous Pulfrich effect. CONCLUSIONS: The results suggest that suprathreshold speed perception is intact in the amblyopic eye when both eyes are open.